Empowering leadership during the COVID-19 outbreak: Implications for work satisfaction and effectiveness in organizational teams - Cremers, Erik Eduard; Curşeu, Petru Lucian (Frontiers in Psychology, 2023)
The COVID-19 pandemic generated unprecedented challenges for social and organizational life. We set out to explore how empowering leadership and leadership support were affected as a result of the team-based organization starting to implement flexible and remote work practices after the outbreak of the COVID-19 pandemic. We collected data in a cross-lagged design and used the two-condition MEMORE mediation procedure to analyze data on work satisfaction and team effectiveness obtained just before and immediately after the COVID-19 outbreak in 34 organizational teams. Our results show that the COVID-19 outbreak did not significantly impact perceptions of empowering leadership or perceived leadership support. However, teams that experienced changes in empowering leadership also reported proportional changes in work satisfaction and effectiveness. Finally, we show that the association between empowering leadership and leadership support, on the one hand, and work satisfaction in teams, on the other hand, is moderated by team size, such that the strength of the association is higher in small rather than large organizational teams. We conclude by arguing that the team-based organization absorbed well the impact and disruptions associated with the COVID-19 outbreak. We also stress the role of empowering leadership as a driver of work satisfaction and the effectiveness of organizational teams.